2017
DOI: 10.1002/bmc.4043
|View full text |Cite
|
Sign up to set email alerts
|

Validated LC–MS/MS method for quantitation of demethylbellidifolin in rat plasma and its application to pharmacokinetic and bioavailability studies

Abstract: Demethylbellidifolin, a major xanthone compound of Swertia davidi Franch, shows many beneficial pharmacological effects including antioxidation, anti-inflammation, anti-fibrosis and cardiovascular protection effects. In this research, a rapid and sensitive LC-MS/MS method for the quantitative analysis of demethylbellidifolin in rat plasma was developed. The demethylbellidifolin and internal standard of aurantio-obtusin were extracted from 50 μL of rat plasma samples with ethyl acetate, then the dried residue w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Choosing an appropriate IS is the key to bioanalysis. A previous study has demonstrated that aurantio‐obtusin is suitable for use as an internal standard owing to its stability, accessibility throughout the whole analysis procedure, extraction efficiency and consistency with the analyte at the retention time (J. Zhang, Yan, Qu, & Zhou, 2018). In order to apply the analytical method for obtusifolin pharmacokinetics and tissue distribution studies, aurantio‐obtusin was selected as the IS for the assay because of its similar retention time and ionization response with obtusifolin.…”
Section: Resullts and Discussionmentioning
confidence: 99%
“…Choosing an appropriate IS is the key to bioanalysis. A previous study has demonstrated that aurantio‐obtusin is suitable for use as an internal standard owing to its stability, accessibility throughout the whole analysis procedure, extraction efficiency and consistency with the analyte at the retention time (J. Zhang, Yan, Qu, & Zhou, 2018). In order to apply the analytical method for obtusifolin pharmacokinetics and tissue distribution studies, aurantio‐obtusin was selected as the IS for the assay because of its similar retention time and ionization response with obtusifolin.…”
Section: Resullts and Discussionmentioning
confidence: 99%